Peningkatan Hasil Belajar Biologi melalui Pendekatan Kontekstual Berbantuan PowerPoint Interaktif: Studi pada Materi Sistem Pernapasan Manusia - Marchelle Nhatanael Walangitan; Herry M. Sumampouw; Anita C. Tengker (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Improving the quality of biology learning in secondary schools requires pedagogical innovations that connect academic content with real-life contexts and leverage digital technology. This study aims to analyze the effect of a contextual teaching approach assisted by interactive PowerPoint on students’ learning outcomes in the human respiratory system topic. A true experimental design with a pretest–posttest control group was employed at SMA Negeri 1 Langowan, involving two eleventh-grade classes selected through simple random sampling. The experimental class received contextual instruction integrated with interactive PowerPoint, while the control class was taught using conventional methods. Data were collected through validated achievement tests and analyzed using normality and homogeneity tests, followed by independent and paired t-tests. The results indicate a significant improvement in learning outcomes for students in the experimental class compared to the control group. The experimental group’s posttest scores were substantially higher, and the difference was statistically significant. Integrating a contextual approach with interactive visualization effectively enhanced students’ understanding of abstract biology concepts, promoted active participation, and strengthened learning motivation. These findings support constructivist theory and highlight the relevance of contextual teaching in science education aligned with the Merdeka Curriculum. The study implies the importance of implementing context-based strategies combined with simple digital media to improve biology learning effectiveness. Future research may explore its impact on non-cognitive skills such as critical thinking and scientific attitudes. Furthermore, the results of this study provide opportunities for teachers to be more creative in designing teaching materials that are not only informative but also interactive and relevant to students' lives. By utilizing media such as interactive PowerPoint, teachers can present complex biological content in a more engaging and understandable way.